2020
DOI: 10.1021/acs.energyfuels.0c00641
|View full text |Cite
|
Sign up to set email alerts
|

Hydrofining Process of Coal Tar Based on Four Kinds of Catalyst Grading

Abstract: Although the mechanism of coal tar hydrogenation technology has not been fully revealed, many enterprises have realized the industrialization of this technology through the reference of crude oil hydrogenation technology. Therefore, it will be very helpful for the development of this technology to present a research result close to industry. Based on four kinds of catalyst gradations, the hydrogenation experiments of different processes and a series of 1200 h long-term experiments were carried out in a four-tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…10 Wang et al 11 reported that the reaction parameters and feed nitrogen could strongly influence the ability of catalysts (NiMo/Al 2 O 3 and NiW/USY). Similarly, Niu et al 12 examined the effects of process conditions chiefly on the product properties. To compete with petroleum-based fuels, many researchers have pursued producing light fraction oils from coal-based oils.…”
Section: Introductionmentioning
confidence: 99%
“…10 Wang et al 11 reported that the reaction parameters and feed nitrogen could strongly influence the ability of catalysts (NiMo/Al 2 O 3 and NiW/USY). Similarly, Niu et al 12 examined the effects of process conditions chiefly on the product properties. To compete with petroleum-based fuels, many researchers have pursued producing light fraction oils from coal-based oils.…”
Section: Introductionmentioning
confidence: 99%
“…The catalyst grading scheme can be based on different catalysts’ physical and chemical properties and their distribution in each reactor. Different catalyst gradations result in a great difference in the activities and selectivities. , The difference in chemical properties is mainly due to the different content of substances in each catalyst, and the differences in physical properties are manifested in the surface area, pore size, and shape . Former studies on HDN reactions mainly used modeling compounds and light oil such as gasoline and diesel oil.…”
Section: Introductionmentioning
confidence: 99%